Global Improvement in Dietary Quality Could Lead to Substantial Reduction in Premature Death. Issue 6 (2nd May 2019) - Wang, Dong D; Li, Yanping; Afshin, Ashkan; Springmann, Marco; Mozaffarian, Dariush; Stampfer, Meir J; Hu, Frank B; Murray, Christopher J L; Willett, Walter C
ABSTRACT: Background: The preventable premature mortality achievable by improvement in dietary quality at a global level is unclear. Objective: The aim of this study was to assess dietary quality globally, and to quantify the potential global impact of improving dietary quality on population health. Methods: We applied the Alternate Healthy Eating Index (AHEI, potential range 0–100) to a global dietary database to assess dietary quality among adults in 190 countries/territories. The relation of AHEI score to risks of major chronic disease was estimated from 2 large cohorts of men and women for whom many repeated dietary assessments during up to 30 years were available. We calculated the preventable premature deaths achievable by shifting from current national diets to a reference healthy diet. Results: The global mean AHEI score in 2017 was 49.5 for males and 50.5 for females. Large differences between current and target intakes existed for whole grains, sodium, long-chain n–3 polyunsaturated fats, polyunsaturated fats, and fruits. From 1990 to 2017, the global mean AHEI score increased modestly from 45.4 to 50.0. Diet quality varied substantially across the world. Coastal Mediterranean nations, the Caribbean region, and Eastern Asia (except China and Mongolia) had a higher AHEI score, whereas Central Asia, the South Pacific, and Eastern and Northern Europe had a lower score. An improvement in dietary quality from the current global diet to the reference healthy diet could prevent >11 million premature deaths, ∼24% of total deaths in 2017. These included 1.6 million cancer deaths, 3.9 million coronary artery disease deaths, 1.0 million stroke deaths, 1.7 million respiratory disease deaths, 0.4 million neurodegenerative disease deaths, 0.5 million kidney disease deaths, 0.6 million diabetes deaths, and 1.2 million digestive disease deaths. Conclusions: Global dietary quality is slowly improving, but remains far from optimal and varies across countries. Improvements in dietary quality have the potential to reduce mortality rates substantially.